Evaluation of Cytotoxicity of Pb2+ Ion-Adsorbed Amino-Functionalized Magnetic Mesoporous Silica Nanoparticles: An In Vitro Study - Chen, Yu; Liu, Miao (Frontiers in Materials, 2022)
Abstract：Application of amino-functionalized mesoporous silica coating core-shell magnetic nanoparticles (Fe3O4@mSiO2-NH2 NPs) for adsorbing heavy metal ions has attracted intensive interests in recent years. Despite the cytotoxicity triggered by the co-exposure of nanoparticles (NPs) and metal ions in relative high dosages has been reported, the effect of the adsorbed heavy metal ions on the cytotoxicity to human cells remains unexplored. Herein, we demonstrated the effect of amino-functionalized Fe3O4@mSiO2 core-shell magnetic nanoparticles before and after adsorbing Pb2+ ions on the cytotoxicity to human kidney cells (HEK293). The surface morphology, viability, oxidative stress (OS) induction of HEK293 cells incubated with Fe3O4@mSiO2-NH2 NPs and Pb2+ ion adsorbed Fe3O4@mSiO2-NH2 NPs were assessed, respectively. Transmission electron microscope (TEM) images of cell sections depicted that Fe3O4@mSiO2-NH2 NPs were internalized by HEK293 cells and gathered mainly in cytoplasm. Cell viability (MTT) assays revealed the Fe3O4@mSiO2-NH2 NPs could enhance the cell viability to 119.9% and 108.2% comparing to the control group, respectively. On contrast, the Pb2+ ions adsorbed Fe3O4@mSiO2-NH2 NPs were toxic to the cell because when the Pb2+ ion contents were 5.0 and 7.5 μg∙mL−1, the viabilities of the samples decreased to 97.1% and 84.7%, respectively. Oxidative stress data proved that OS was negatively affected by both dissociative Pb2+ ions and the Pb2+ ions adsorbed Fe3O4@mSiO2-NH2 NPs. The cytotoxicity may be attributed to the OS induced by Pb2+ ions leaked from the adsorbent. Under the same Pb2+ ion concentration, the cytotoxicity of the adsorbed Pb2+ ions was lower than that of the dissociative Pb2+ ions, indicating that the adsorption by NPs inhibited the cytotoxicity of Pb2+ ion. This work will provide new references for assessing the cytotoxicity of Pb2+ adsorbed nanoparticles.